2022
DOI: 10.1002/ags3.12593
|View full text |Cite
|
Sign up to set email alerts
|

Significant positive impact of duodenum‐preserving pancreatic head resection on the prevention of postoperative nonalcoholic fatty liver disease and acute cholangitis

Abstract: Aim: This study aimed to compare the incidence of postoperative nonalcoholic fatty liver disease (NAFLD), postoperative cholangitis, and fibrosis-4 (FIB)-4 index in patients who underwent duodenum-preserving pancreatic head resection (DPPHR) and pancreaticoduodenectomy (PD) for low-grade malignant tumors and verify the usefulness of DPPHR in preventing the occurrence of these disorders. Methods: This retrospective study included 70 patients who underwent PD (n = 39) and DPPHR (n = 31) between 2006 and 2018 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 40 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…However, Kato et al compared the incidence of short-term complications in patients with low-grade malignant tumors treated with DPPHR and PD, and reported no difference in the incidence of short-term complications such as pancreatic stula. Moreover, they also reported a signi cantly lower incidence of postoperative cholangitis in the long term [11]. Horiguchi et al also reported that postoperative endocrine and exocrine functions were signi cantly preserved in the DPPHR group compared to the PD group [7].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, Kato et al compared the incidence of short-term complications in patients with low-grade malignant tumors treated with DPPHR and PD, and reported no difference in the incidence of short-term complications such as pancreatic stula. Moreover, they also reported a signi cantly lower incidence of postoperative cholangitis in the long term [11]. Horiguchi et al also reported that postoperative endocrine and exocrine functions were signi cantly preserved in the DPPHR group compared to the PD group [7].…”
Section: Discussionmentioning
confidence: 93%
“…The surgical technique for DPPHR was described in a previous study [11]. Brie y, it involves: 1) Dissection of gastric and duodenocolic ligaments without Kocher's maneuver to preserve the drainage veins from duodenum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that the cause of NAFLD after PD was malnutrition [ 19 ]. Kato et al [ 20 ] reported that the serum albumin level in the DPPHR group were significantly better than that in the PD group (4.2 vs. 3.9; P = 0.003), the prognostic nutritional index of the DPPHR group was better (albeit the difference was not significant), and the incidence of postoperative NAFLD in the DPPHR group was also lower than that in the PD group. As LDPPHR can better maintain the continuity of the stomach-duodenum-bile duct, LDPPHR offers more advantages than LPD in terms of postoperative gastrointestinal function recovery and nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…7,[73][74][75][76][77][78][79] Regarding the comparison of short-term postoperative complications between DPPHR (n = 21) and PD (n = 19), Horiguchi et al 7 found no significant differences in operative time, blood loss, complications, or hospital stay. Kato et al 80 also reported no significant difference in the frequency of postoperative complications, including pancreatic fistula, when DPPHR (n = 34) was compared with subtotal preserving pancreaticoduodenectomy (SSPPD) (n = 41).…”
Section: Clinical Advantage Of Dpphr Compared With Pancreaticoduodene...mentioning
confidence: 99%